Antarctic environmental protection: Strengthening the links between science and governance. Issue 83 (May 2018) - Hughes, Kevin A.; Constable, Andrew; Frenot, Yves; López-Martínez, Jerónimo; McIvor, Ewan; Njåstad, Birgit; Terauds, Aleks; Liggett, Daniela; Roldan, Gabriela; Wilmotte, Annick; Xavier, José C.
Highlights: Antarctica's scientific and intrinsic values are worthy of protection. Antarctic Treaty System bodies have and are taking action to protect these values. Much Antarctic science is done that is relevant to environmental policy discussions. Environmental benefits will result from greater science-policy interaction. Mechanisms linking evidence and governance could be strengthened and better funded. Abstract: The Antarctic has significant environmental, scientific, historic, and intrinsic values, all of which are worth protecting into the future. Nevertheless, the area is subject to an increasing level and diversity of human activities that may impact these values within marine, terrestrial and cryosphere environments. Threats to the Antarctic environment, and to the aforementioned values, include climate change, pollution, habitat destruction, wildlife disturbance and non-native species introductions. Over time, a suite of legally binding international agreements, which form part of the Antarctic Treaty System (ATS), has been established to help safeguard the Antarctic environment and provide a framework for addressing the challenges arising from these threats. Foremost among these agreements are the Protocol on Environmental Protection to the Antarctic Treaty and the Convention on the Conservation of Antarctic Marine Living Resources. Many scientists working in Antarctica undertake research that is relevant to Antarctic environmental policy development. More effective two-way interaction between scientists and those responsible for policy development would further strengthen the governance framework, including by (a) better communication of policy makers' priorities and identification of related science requirements and (b) better provision by scientists of 'policy-ready' information on existing priorities, emerging issues and scientific/technological advances relevant to environmental protection. The Scientific Committee on Antarctic Research (SCAR) has a long and successful record of summarizing policy-relevant scientific knowledge to policy makers, such as through its Group of Specialists on Environmental Affairs and Conservation (GOSEAC) up to 2002, currently the SCAR Standing Committee on the Antarctic Treaty System (SCATS) and recently through its involvement in the Antarctic Environments Portal. Improvements to science-policy communication mechanisms, combined with purposeful consideration of funding opportunities for policy-relevant science, would greatly enhance international policy development and protection of the Antarctic environment.